Projekt STEP - korak na obrobje - Edelman, Joshua (Amfiteater (Ljubljana), 2015)
This article presents the Project on European Theatre Systems (STEP) and its most recent research into the theatre lives of smaller European cities. It situates STEP's research in the tradition of sociological, philosophical and psychological inquiry into the arts' function within society and, in particular, into audience research. It explains, however, the particular benefits of STEP's approach and methodologies: that they enable international comparison and shift attention from the extraordinary performances favoured by theatre scholars to the ordinary ones that contribute to the bulk of spectators' experiences of theatre. The article explains the methods of the STEP City Study and surveys how its results will be presented in the rest of this special issue.
Keywords: arts policy; gledališče; gledališki sistemi; gledališko občinstvo; international comparative theatre survey; mednarodne primerjave; recepcija občinstva; reception research; STEP; theater; theater sociology; theatre audience